(3eONd eaGgjej h JWHjbjs - (3MejO YHO GdfHj(B, (3GdWGFjs ((3YeGf(B:s (3OGQ caGAI GdeYQaI ddfTQ hGdJhRjY(B,s, 2022)
(3jbOe cJGH (B"(3GdJShjb GdEdcJQhfj aj bWGY GdNOeGJ(B" (3OQGSI JWHjbjI TGedI heJYebI Mhd CMOK CSGdjH GdJShjb GdQbej aj GdbWGYGJ GdNOejI GdQFjSjI aj GdCQOf, eKd GdeSJTajGJ hGdeUGQa hGdafGOb hTQcGJ GdWjQGf(B. (3jJejR gPG GdcJGH HOeLg GdQGFY Hjf GdfXQjI hGdJWHjb, MjK jSJYQV GdeDda GdeaGgje GdCSGSjI ddJShjb GdEdcJQhfj Ke jfJbd Edi JMdjd Yedj dYfGUQ GdeRjL GdJShjbj GdSHGYj aj gPg GdbWGYGJ(B. (3hef NdGd gPg GdOQGSI GdejOGfjI, jbOe GdcJGH QDi bjeI Mhd cjajI JWHjb COhGJ GdJShjb GdQbej HcaGAI dJMbjb fJGFL edehSI aj GdbWGY GdNOej(B. (3ceG jSdW GdVhA Ydi GdJMOjGJ hGdaQU GdJj JhGLg gPg GdbWGYGJ aj Xd GdJMhd GdQbej GdeJSGQY(B. s
(3GdeQGLY U(B.219s
Keywords: (3GdJShjb GdEdcJQhfj (B- (3GdNOeGJs